THE STUDY ON SIMILE IN PĀLI LITERATURE: Types and Its Significances) - Medhacitto, Tri Saputra; Makuruppe Dhammananda; Sanu Mahatthanadull (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This research aims to study the use of similes in the Pāli Literature, analyzing their types and their significance. It is qualitative research that is carried out with a library approach, by collecting the data from primary sources like Tipiṭaka and other Pāli treatises as well as secondary sources such as books, journals, and academic articles. By utilizing this method, this research collects the data relevant to the topic and examines it to produce a comprehensive study of the similes in the Pāli Literature, discovering the types and their significance. Simile (upamā) is a figure of speech comparing two things, showing the similarities. In Pāli literature, the simile is used for two functions as a decorative or embellishment (alaṅkāra) of the language and as a means used to convey the meaning of philosophical teaching (atthassa viññāpanāya) or to elucidate the meaning (atthasandassanī). Subodhālaṅkāra provides valuable information for the types of similes identified from the Buddhist perspective. Examining the Sutta Pitaka, it is discovered many types of similes have been used by the Buddha which can be classified according to their nature and characteristics such as similes on nature, similes on animals, similes on person, and similes on material. The Buddha’s use of simile as a teaching method demonstrates his skillfulness in his teaching approach. The use of similes in teaching methods plays a significant role in creating an effective learning process that enables the students to understand the lesson easily.